THE IMPACT OF SENSORY MARKETING ON CUSTOMER SATISFACTION AND REPURCHASE INTENTION (Study Case in Grand Kartika Hotel Restaurant Pontianak) - PALUPI, NURUL DILAH PALUPI B1024141015 (Jurnal Manajemen Update, 2018)
The aim of this research is to analyze the impact of sensory marketing dimensions on customer satisfaction and repurchase intention in Grand Kartika Hotel Restaurant in Pontianak. The data is obtained from distributing the questionnaires to the restaurant customers based on the convenience sampling method, and the data is evaluated by Structural Equation Model (SEM).According to the analysis, the result shows that Hypothesis 1 is accepted where there is a positive relationship and significant impact of sight sense on customer satisfaction. Hypothesis 2 is accepted where there is a positive relationship and significant impact of sound sense on customer satisfaction. Hypothesis 3 is rejected where there is a positive relationship but not significant impact between smell sense and customer satisfaction. Hypothesis 4 is accepted where there is a positive relationship and significant impact of taste sense on customer satisfaction. Hypothesis 5 is rejected where there is a positive relationship but not significant impact between touch sense and customer satisfaction. Hypothesis 6 is accepted where there is a positive relationship and significant impact of sight sense on repurchase intention. Hypothesis 7 is accepted where there is a positive relationship and significant impact of sound sense on repurchase intention. Hypothesis 8 is accepted where there is a positive relationship and significant impact of smell sense on repurchase intention. Hypothesis 9 is accepted where there is a positive relationship and significant impact of taste sense on repurchase intention. Hypothesis 10 is rejected where there is a positive relationship but not significant impact between touch sense and repurchase intention. Hypothesis 11 is rejected where there is a significant impact but negative relationship between customer satisfaction and repurchase intention.Keywords: Sensory Marketing, Customer Satisfaction, Repurchase Intention, Restaurant, Structural Equation Model (SEM)